Secondary Cerebral Folate Deficiency Comorbidity in Neuronal Ceroid Lipofuscinosis - Lim, Yvonne Yijuan; Tapawan, Sarah Jane Corpuz; Pang, Aileen Yu-Wen; Hyland, Keith; Tay, Stacey Kiat-Hong (Journal of Pediatric Neurology, 2016)
Secondary cerebral folate deficiency (CFD) has been described in various neurodegenerative diseases, for example, Aicardi–Goutieres syndrome, Kearns–Sayre syndrome, and other mitochondriopathies. The importance of associated CFD lies in the possibility that treatment with folinic acid may improve the outcome of these diseases, or its presence may affect the course of the disease. We describe a patient with neuronal ceroid lipofuscinosis (NCL) type 2 due to tripeptidyl-peptidase I (TPP1) deficiency with an atypical presentation of chorea and dystonia. She was subsequently found to have low cerebrospinal fluid (CSF) 5-methyltetrahydrofolate (5-MTHF). TPP1 level in skin fibroblast cultures was < 0.1 nmol/min/mg protein (normal range: 0.7–2.2 nmol/min/mg protein), confirming the diagnosis of NCL. CSF 5-MTHF was 36 nmol/L (normal range: 40–150 nmol/L) while red blood cell folate was slightly elevated at 1,902 nmol/L (normal range: 776–1,784 nmol/L). Oral folinic acid was administered with no clear amelioration of the movement disorder. This is the first documented case of low CSF folate levels in NCL. Given the unusual clinical presentation of dyskinesia, it is possible that low CSF 5-MTHF levels may have contributed to this. It is important to evaluate CSF 5-MTHF levels in patients with NCL as low cerebral folate levels may aggravate the neurodegenerative process.
Keywords: neuronal ceroid lipofuscinosis; methyltetrahydrofolate; folate deficiency